Emergent Technologies for Active Aging - Baldissera, Thais Andrea; De Faveri, Cristiano (Revista ComInG - Communications and Innovations Gazette, 2016)
Continuous advances in medicine and wellness areas have contributed to an active and enjoyable aging. The use of technology in assisting elderly community is expected to have a positive contribution to support the diversity of required services that promote independent living. Most initiatives in this area are intrinsically focused on providing health-care services to senior citizens. However, a broader perspective of the aging process is required, which is conceptually described as ”active aging”. In this paper, we present some prominent technologies based on context-awareness and Internet of Things that may assist elderly people in different needs during a productive live. We exemplify the applicability of such technologies by describing a scenario in which daily activities are performed by an elderly assisted by her son.